Potential Pitfalls of the Humanized Mice in Modeling Sepsis. (2nd September 2018) - Laudanski, Krzysztof; Stentz, Michael; DiMeglio, Matthew; Furey, William; Steinberg, Toby; Patel, Arpit
Abstract : Humanized mice are a state-of-the-art tool used to study several diseases, helping to close the gap between mice and human immunology. This review focuses on the potential obstacles in the analysis of immune system performance between humans and humanized mice in the context of severe acute inflammation as seen in sepsis or other critical care illnesses. The extent to which the reconstituted human immune system in mice adequately compares to the performance of the human immune system in human hosts is still an evolving question. Although certain viral and protozoan infections can be replicated in humanized mice, whether a highly complex and dynamic systemic inflammation like sepsis can be accurately represented by current humanized mouse models in a clinically translatable manner is unclear. Humanized mice are xenotransplant animals in the most general terms. Several organs (e.g., bone marrow mesenchymal cells, endothelium) cannot interact with the grafted human leukocytes effectively due to species specificity. Also the interaction between mice gut flora and the human immune system may be paradoxical. Often, grafting is performed utilizing an identical batch of stem cells in highly inbred animals which fails to account for human heterogeneity. Limiting factors include the substantial cost and restricting supply of animals. Finally, humanized mice offer an opportunity to gain knowledge of human-like conditions, requiring careful data interpretation just as in nonhumanized animals.